MgBr2-mediated ionic Diels-Alder reaction of acetals of alpha,beta-unsaturated aldehydes and ketones with 1,3-dienes - Chavan, Subhash P.; Ethiraj, Krishna S.; Dantale, Shubhada W. (Synthetic Communications, 2007)
A facile, mild, and efficient methodology for the ionic Diels-Alder reaction of acetals of alpha,beta-unsaturated ketones and aldehydes as dienophiles with various 1,3- dienes employing MgBr2 as the Lewis acid catalyst to furnish corresponding Diels-Alder adducts at ambient temperature is described.
Keywords: acetals; Catalysts; Diels-Alder reactions; dienes

Multi-step synthesis of miltefosine: integration of flow chemistry with continuous mechanochemistry - Patil, Niteen B.; Atapalkar, Ranjit S.; Chavan, Subhash P.; Kulkarni, Amol A. (Chemistry-A European Journal, 2021)
Herein we report for the first time, an advanced continuous flow synthesis of the blockbuster Leishmaniasis drug miltefosine from simple starting materials by a sequence involving four steps of chemical transformation including a continuous mechanochemical step. First three reaction steps were performed in simple tubular reactors in a telescopic mode, while in the last step the product precipitated from the 3(rd) step was used for a continuous mechanochemical synthesis of miltefosine. When compared to a typical batch protocol that takes 15 h, miltefosine was obtained in 58 % overall yield in flow synthesis mode at the laboratory scale in a total residence time 34 min at synthesis rate of 10 g/hr, which is sufficient to treat 4800 patients per day.
Keywords: continuous flow; continuous mechanochemistry; miltefosine; multistep synthesis; reactive intermediates